The South African general anti-tax avoidance rule and lessons from the first world: a case law approach - Pidduck, Teresa Michelle Calvert (Rhodes University, Faculty of Commerce, Department of Accounting, 2018)
Tax avoidance has been a concern to revenue authorities since the time that the concept of tax was first introduced. Revenue authorities worldwide constantly strive to ensure taxpayer compliance, while combating impermissible tax avoidance. South Africa uses a general anti-avoidance rule (GAAR) as part of its arsenal to combat the increasingly innovative ways in which taxpayers seek to minimise their tax. However, the GAAR has been the source of much criticism and its effectiveness in combatting impermissible tax avoidance is untested in the courts. Therefore, the use of hindsight to criticise the GAAR is not possible. This study applied a qualitative approach to compare the South African, Australian and Canadian GAARs in order to propose changes which are intended to improve the efficacy of the South African GAAR. This research was performed by first comparing the three GAARs using a doctrinal research methodology and then applying the South African GAAR to the facts of selected cases from Australia and Canada in the form of reform-oriented research. In order to apply the South African GAAR to the facts of the cases a framework was developed in phase 1 of the research in order to ensure consistency in the application. This allowed for a more reliable analysis to be made regarding the areas where the South African GAAR could be improved. The convergence of results from the two research methodologies validated many of the suggestions made for the improvement of the South African GAAR This thesis examined the GAARs in South Africa, Australia and Canada with a view to identifying if there are any lessons to be learned for their application and interpretation, in order to suggest improvements which can be made to the South African GAAR. Further, relevant Australian and Canadian case law was found to be instructive as to the approach that could be adopted for purposes of applying the South African GAAR. The findings of the research revealed that while the South African, Australian and Canadian GAARs differ in their structure, each is directed to achieve the same end. The results of the study identified two types of improvements to the South African GAAR. Firstly, the South African GAAR should be consolidated into a three-part enquiry instead of the current four-part enquiry. In doing so the tainted elements (previously the abnormality requirement) could be used to inform an objective test of purpose. Secondly, guidance on areas of uncertainty regarding the application of the South African GAAR needs to be provided in order to prevent possible inconsistent judicial interpretations that may limit the efficacy of the GAAR whilst still protecting the right for taxpayers to legitimately minimise their tax burdens. One additional cause for concern highlighted in this research is the use of provisions from other jurisdictions without guidance on the application in the South African context. The use of similar provisions to that of its much-criticised predecessor has also introduced areas of uncertainty regarding the application of the South African GAAR. These areas of weakness and uncertainty arguably prevent the South African GAAR from being an effective deterrent to tax avoidance and many could be addressed by the legislature.
Keywords: Tax evasion -- South Africa; Taxpayer compliance -- South Africa; Taxation -- Law and legislation -- South Africa; South Africa. Income Tax Act, 1962; Taxation -- Law and legislation -- Australia; Taxation -- Law and legislation -- Canada; Tax evasion -- Law and legislation -- South Africa; General anti-avoidance rule (GAAR)